2003
DOI: 10.1007/s00330-003-1851-6
|View full text |Cite
|
Sign up to set email alerts
|

CT findings and serum ca 125 levels in malignant peritoneal mesothelioma: report of 11 new cases and review of the literature

Abstract: The aim of this study was to review and reappraise the clinical and CT features of malignant peritoneal mesothelioma (MPM), and to discuss differential diagnosis. The history, clinical, and laboratory data, and imaging studies of 11 patients with a histologically proven diagnosis of MPM, were retrospectively reviewed. Our patients consisted of 7 women and 4 men, with a median age of 48 years (age range 40-55 years). There was a definite history of significant asbestos exposure in 6 patients. Abdominal swelling… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
28
1
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(32 citation statements)
references
References 22 publications
1
28
1
1
Order By: Relevance
“…Kebapci M et al 19 reported smooth thickening (36%) and irregular thickening (64%) in MPM. Charoensak A et al 6 reported smooth thickening (13.9%) and irregular thickening (48.8%) in PC.…”
mentioning
confidence: 96%
See 1 more Smart Citation
“…Kebapci M et al 19 reported smooth thickening (36%) and irregular thickening (64%) in MPM. Charoensak A et al 6 reported smooth thickening (13.9%) and irregular thickening (48.8%) in PC.…”
mentioning
confidence: 96%
“…The pleated appearance shows soft tissue thickening of the leaves of the mesentery. In prior studies, the mesentery was involved in 9 of 11 DMPM patients, 19 while it was involved in 20 patients of 53 PC patients. 6 Similarly, 18 DMPM patients (37.5%) showed thickening of the mesentery, while only four PC patients (8.51%) showed thickening of the mesentery in our study.…”
mentioning
confidence: 98%
“…Calcified plaques are less frequent in MPM than in pleural mesothelioma, but calcified pleural plaques and other signs associated with asbestos exposure may exist in the chest in up to 50% of patients with MPM [20]. In a previously published study, pleural changes, such as calcification or thickening, were found in a high proportion (65%) of patients with MPM [21]. In the present study, radiological evaluation revealed evidence of pleural calcification/plaques in 51% of the patients and pleural thickening in 20%, which is in accordance with the literature.…”
Section: Discussionmentioning
confidence: 99%
“…Most of the research on serum markers have been done in pleural mesothelioma, with some patients shown to have elevations in CA-125, alpha fetoprotein, CEA, mesothelin, osteopontin, and fibulin-3. Unfortunately, their sensitivities are too low to be used for diagnostic purposes (28,(33)(34)(35). Levels of serum mesothelinrelated protein (SRMP) have shown more promise, with a sensitivity of 60% (7,36).…”
Section: Diagnosismentioning
confidence: 99%
“…The lack of a primary site with neither lymph node involvement nor distant metastases helps differentiate MPM from other intra-abdominal malignancies (27). Ascites is found in 60-100% of patients that are newly diagnosed (28,29). Other findings include caking, thickening or masses in the omentum, mesenteric nodules, peritoneal thickening, diaphragmatic involvement, scalloping of the intraabdominal organs such as the liver and spleen, and loculated ascites (30,31).…”
Section: Diagnosismentioning
confidence: 99%